Evaluation of oats and annual ryegrass intercropped with cool-season legumes - Fontaneli, Renato Serena; Freire Júnior, Ney (Pesquisa Agropecuaria Brasileira, 1991)
A field experiment was carried out at the University of Passo Fundo (UPF), Passo Fundo, RS, Brazil, to evaluate mixtures of oats and ryegrass (annual species) intercropped with cool-season legumes, in terms of total dry matter yield (DM) and crude protein (CP) content and yield. The treatments were: 1. oats (OA) (Avena saliva L.) cv. UPF-10 + ryegrass (RY) (Lolium multiflorum Lam.) cv. Comum; 2. OA + RY + commom vetch (Vicia saliva L.) cv. Comum; 3. OA + RY + subterraneum clover (Trifolium subterraneun L.) cv. Trikkala; 4. OA + RY + red clover (T. pratense L.) cv. Kenland; 5. OA + RY + arrowleaf clover (T. vesiculosum Savi) cv. Yuchi and 6. OA + RY + white clover (T. repens L.) cv. Yi. Cuttings were applied from July 1987 to February 1988. Oats + ryegrass + white clover, oats + ryegrass + red clover and oats + ryegrass + commom vetch intercrops showed the greatest DM yields. For the spring seeding of soybean or maize crops, mixtures with commom vetch or subterraneum clover are suitable, mainly to improve herbage quality during the critical cool-season period. Mixtures average CP content was high (15,8%).